Strategi Agen Asuransi Syariah Dalam Meningkatkan Jumlah Nasabah - Nuri Aslami; Aulia Monica (VISA: Journal of Vision and Ideas, 2021)
The result of this review is to decide on specialist procedures in expanding the number of clients, among others, through specialists who have techniques in expanding the market, especially for individuals who have not used sharia protection administration through direct socialization, following and working on existing business sectors by trying to consistently maintain correspondence with clients in control to provide the best support, prepare finances and endanger executives in sharia protection, choose risk for members by distinguishing the possibility of danger events seen by members, assess and estimate the magnitude of harm that may occur and decide the best strategy to face the dangers that have occurred. Keywords: Agent Strategy, Sharia Insurance, Increasing Customers